Halleck, Henry Wager (Tufts Archival Research Center, 2008)
"Halleck, Henry Wager 1815-1872; Military advisor to the Pres. with title of General-in-Chief July 11, 1862- Mar. 12 1864." Produced by: Joseph Ward, 125 Washington Street, Boston. These dates are approximate.